Initial Hierarchy Weighting and Score vs Activities - Smith, Jeremy (Cranfield University, 2017)
This is an initial excel file with weightings for the Maslow Hierarchy and scores vs campaign activities. The Maslow Hierarchy has been applied to a generic situation conflict by examining the levels and assessing the impact of military and other actions on the elements of this hierarchy. This is basically the format of the matrix. The left hand axis is the Maslow hierarchy - each layer of which is weighted. The columns are the list of actions in the campaign. the entries are then refer each action to each Maslow line. The matrix is a first draft and the intent is to determine the utility of this in modelling campaigns and in terms of the consistency of the scores and weightings. The idea is then to produce a quantified interconnected model which allows a change in one input to affect a specific element of the Maslow hierarchy and then an outcome in terms of a positive or negative effect on ‘perception’ is generated. There is then a linkage to the use of the Cranfield RCAT wargame which uses these types of information.
Keywords: 'maslow'; 'Sociology'